The Influence of Islamic Store Atmosphere, Service Quality and Digital Marketing on Consumer Purchase Decisions - Afri Tia Deftiana; Asyari (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the extent to which the store atmosphere characterized by Islamic values, service quality, and digital marketing strategies influences consumers' purchasing decisions at Foresthree Coffee Shop. The background of this study is based on the rapid growth of the coffee shop industry and the shift in consumer tastes that now prioritize a comprehensive experience not only on the taste of coffee, but also the comfort of space, quality of service, and digital interaction. A quantitative approach was applied in this study using a survey method of 460 respondents from five favorite coffee shops in Bukittinggi City. The collected data was then analyzed using descriptive statistics and multiple linear regression. The findings of the study show that the three variables of the Islamic atmosphere, service quality, and digital marketing have a positive and significant effect on purchasing decisions. The presence of Islamic elements in store design fosters a sense of comfort and increases the confidence of Muslim consumers (β = 0.232; p = 0.000). On the other hand, responsive and friendly service strengthens the level of customer satisfaction (β = 0.268; p = 0.000). The digital marketing strategy through social media and online platforms has proven to be effective in expanding brand reach and strengthening relationships with consumers (β = 0.130; p = 0.007). Overall, these three factors contributed 23.1 percent to the purchase decision variable (R²= 0.231). Based on these results, business actors are advised to integrate Islamic elements into the concept and atmosphere of the store, maintain and improve the quality of service consistently, and optimize the use of digital channels to strengthen customer loyalty